PERAN DUKUNGAN ORGANISASI DAN BERSYUKUR TERHADAP KETERIKATAN KERJA (STUDI PADA KARYAWAN PERUSAHAAN XY) - Suyasa, Putu Tommy Y.S; Mangarondang, Meina Evelin; Rostiana, Rostiana (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2023)
This study aims to study at the role of perceived organizational support and gratitude towards work engagement. Work engagement refers to individual involvement and satisfaction with enthusiasm at work (Schaufeli, 2013). With good work engagement, Workers are expected to work optimally in difficult situations such as those experienced by workers during the WFH period related to the COVID-19 pandemic. To support the needs of work in undergoing the WFH period, XY Company Management has provided several forms of convenience and assistance. A work environment that supports employees to work well can be seen as a Perceived of Organizational Support. In this study, the researcher will involve other aspects of the Worker's inner self that can affect work engagement but are rarely researched, gratitude. This research is a quantitative study with data collection methods using convenience sampling techniques. From research conducted on 64 participants (27 women and 37 men) using the Spearman 's rho correlation test, it was found that both perceived organizational support and gratitude have roles in work engagement. In the condition of the COVID-19 pandemic, gratitude can be a factor that explains why individuals have work engagement.